Comparative Study On Characteristics Of Solid Waste Black Water In Strait Meranti Islands - Natali, Alvin; Siregar, Yusni Ikhwan; Siregar, Sofyan Husein (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The amount of solid waste at station 1 to station more than 2 type of solid waste in the Black Water Strait of each station is almost the same, where the Black Water Strait is dominated by the type of waste plastic and small pieces of wood. In Black Water Strait encountered type of waste that generally consist of plastics, paper, rubber, foam, jute sacks, leaves, and small pieces of wood. From this we can conclude that the solid waste at both stations originate from the same source ie domestic waste. The strong tidal currents provide a direct influence on the amount of solid waste that are found in every point of the study and vice versa if the lower the pressure, the current is the entry-level waste into gear tends to be decreased.Keywords : Comparative Study, Solid Waste, Selat Air Hitam, Meranti Island